Social Support and Help-Seeking For Suicidal Ideation in Educational Institution-Based Menfess in Application X - Caroline, Ribka; Triana, Lidya (Green Publisher Indonesia, 2025)
Suicide incidents among students are increasingly common in Indonesia. On social media, anonymous statements of suicidal ideation have also emerged, especially on the X platform using the autobot feature or in Indonesia known as menfess, some of which are associated with educational institutions. Statements that emerge from menfess are anonymous, and statements of suicidal ideation on menfess associated with educational institutions often get responses from menfess members or users of the X application who are exposed. Studies on social support that emerges in menfess and suicidal ideation, especially for stigmatized issues such as suicide in Indonesia, are still very limited. Based on the theory of the strength of weak ties from Granovetter (1973), this study aims to study the possibility of menfess space as a place for those with suicidal ideation to express their feelings, and get social support, so that menfess can becomes a promotive and preventive forum for suicidal ideation using a qualitative approach and analyzed through Content Analysis.